The implications of serum enzymes and coagulation activities in postinfarction myocardial - Yuan,Shi-Min (2011)
OBJECTIVE: Associations between cardiovascular diseases and serum enzymes or coagulation activities have been sufficiently documented in patients with myocardial infarction. However, the alterations of these biomarkers in patients with postinfarction myocardial rupture have rarely been reported. The aim of this study is to present the profiles of the markers in patients with postinfarction myocardial rupture. METHODS: From 2004 to 2008, 19 consecutive patients were referred to this hospital for surgical repair of postinfarction myocardial rupture. Eight (42.1%) patients had free wall rupture, 5 (26.3%) had papillary muscle rupture, 5 (26.3%) had ventricular septal rupture, and 1 (5.3%) had double structure (ventricular septum + free wall) rupture. Thirteen patients survived the operation, and 6 died. Laboratory findings including serum enzymes and coagulation activities were collected and analyzed. RESULTS: The coagulation markers and serum enzymes except for fibrinogen increased significantly after the development of myocardial rupture. Statistical differences in D-dimer, partial thromboplastin time, peak lactate dehydrogenase, peak creatine kinase and creatine kinase fraction MB were found between non-survivors and survivors. Troponin I values were elevated significantly during the early days after the onset or surgical repair of myocardial rupture. Multivariant regression analysis did not show any significant relationship between creatine phosphokinase fraction MB (Y) and D-dimer (X1) or fibrinogen (X2). CONCLUSION: Myocardial rupture leads to extremely high serum enzyme and coagulation activities except for fibrinogen after the onset. The evaluation of these biomarkers may help in making diagnostic and treatment decisions and in judging the clinical prognosis of such patients.